GLOBAL CITEZENSHIP EDUCATION MEMBENTUK MASYARAKAT CYBERCOMMUNITY - Ansori, Makruf; Talbase, Muaimin (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
The global citizen education word if it is meant to mean global public education that aims to make global society more wise in menajalankan kehidupannnya and still in accordance with the norms of life. The term